Induction of glutamate binding sites in hippocampal membranes by transient exposure to high concentrations of glutamate or glutamate analogs - Kessler, M (J Neurosci, 1986)
The number of Na+-independent, Cl--dependent glutamate binding sites in rat hippocampal membranes is increased two- to fourfold after pre- exposing isolated membranes or hippocampal slices to high concentrations (0.1–10 mM) of L-glutamate or of glutamate analogs with high affinity for this binding site, such as quisqualate, homocysteate, or aminoadipate. N-Methylaspartate and kainate are ineffective. A similar binding increase is induced by transient exposure to the dipeptide tyrosylglutamate. The newly induced binding sites appear to be identical with pre-existing Cl--dependent binding sites by several criteria: They have a similar pharmacological profile, they are sensitive to low concentrations of Na+, and the number of sites can be further increased by transient exposure to micromolar calcium concentrations. Moreover, binding of [3H]APB, a ligand selective for the Cl--dependent glutamate binding sites, is also increased after glutamate preincubation. The induction of binding sites by high glutamate concentrations, described herein, is calcium-independent, not inhibited by leupeptin and, therefore, different from the previously described activation of binding sites by a calcium-sensitive protease. The high concentration of ligand needed to induce increased binding suggests the presence in hippocampal membranes of a binding site with low, millimolar affinity that is functionally related to the known high- affinity binding sites. Several interpretations of the observed effects and their implications for the possible relationship between the binding site and the synaptic receptor are discussed.